A constant threat for HIV: Fc-engineering to enhance broadly neutralizing antibody activity for immunotherapy of the acquired immunodeficiency syndrome. - Nimmerjahn, Falk (European journal of immunology, 2015)
Passive immunotherapy with polyclonal or hyperimmune serum immunoglobulin G (IgG) preparations provides an efficient means of protecting immunocompromised patients from microbial infections. More recently, the use of passive immunotherapy to prevent or to treat established infections with the human immunodeficiency virus (HIV) has gained much attention, due to promising preclinical data obtained in monkey and humanized mouse in vivo model systems, demonstrating that the transfer of HIV-specific antibodies can not only prevent HIV infection, but also diminish virus load during chronic infection. Furthermore, an array of broadly neutralizing HIV-specific antibodies has become available and the importance of the IgG constant region as a critical modulator of broadly neutralizing activity has been demonstrated. The aim of this review is to summarize the most recent findings with regard to the molecular and cellular mechanisms responsible for antibody-mediated clearance of HIV infection, and to discuss how this may help to improve HIV therapy via optimizing Fcγ-receptor-dependent activities of HIV-specific antibodies.